WDM technologies : optical networks. - Dutta, Achyut K.; Dutta, Niloy K., 1953-; Fujiwara, Masahiko (Elsevier Academic Press, 2004)
Internet information (which is doubling every six months) travels through optical fibers. Today, optical fibers are being installed where a single fiber has the ability to carry information as much as 200 times faster than was possible just five years ago. This revolutionary capability is being achieved with technology known as wavelength division multiplexing WDM). WDM technology relies on the fact that optical fibers can carry many wavelengths of light simultaneously without interaction between each wavelength. Thus, a single fiber can carry many separate wavelength signals or channels simultaneously. The communications industry is at the onset of new expansion of WDM technology necessary to meet the new demand for bandwidth. This book deals with the Networks facet of this field (present and future). * Allows engineers working in optical communications(from systems to components) to understand the principles and mechanics of each key component they deal with for optical system design. * Provides an excellent resource for engineers and researchers engaged in all aspects of fiber optic communications, such as optoelectronics, equipment/system design, and manufacturing. * Provides comprehensive coverage of key concepts in optical networks and their application in commercial systems.